The Association of Objectively Measured Daily Life Physical Activity with Anxiety Symptoms in Obese Adults - Zakzagki, Μαρίνα; Kalavrou, Χριστίνα; Krommidas, Χαράλαμπος; Galanis, Ευάγγελος; Hatzigeorgiadis, Αντώνης; Theodorakis, Γιάννης; Morres, Ιωάννης Δ. (Inquiries in Physical Education and Sport, 2021)
Obesity is a chronic, serious prevalent disease, which is often linked to anxiety disorders. Physical activity (PA) is typically used to decrease anxiety symptoms, but obese adults experience sedentary lifestyle. The purpose of this study was to examine if objectively measured PA and sedentary lifestyle are related with lower anxiety symptoms in obese adults. General population participants were recruited on the basis of the following inclusion criteria: (1) adults 18-65 years old; (2) ability for ambulatory movement; (3) Body Mass Index (BMI) ≥ 30 kg/m2. A total of 47 obese adults were included with a mean age of 46.55 ± 10.94 years and BMI 35.05 ± 5.89 kg/m2, indicating class-II obesity. To objectively record PA and sedentary time in daily life, participants wore triaxial accelerometer devices at the right hip for 7 consecutive days and immediately after day-7 completed the State-Trait Anxiety Inventory (STAI), which measures symptoms of state and trait anxiety. Correlation analysis examined the relationship of objectively recorded PA with anxiety. Regression analysis investigated if objectively measured daily life PA and sedentary time predict lower trait anxiety. Results showed that accelerometers were worn for an average of 6.25 days and 13.24 hours per day and recorded moderate intensity PA of 29.79 ± 24.96 minutes per day, which indicates a physically active lifestyle. There was a statistically significant negative relationship between sedentariness and anxiety. Regression analysis showed that only objectively recorded sedentary time, but not PA, was a significant predictor, contributing to lower trait anxiety scores. In conclusion, sedentariness appears to be associated with reduced trait anxiety symptoms in physically active obese adults. These findings suggest the important contribution of sedentary time to the prediction of lower symptoms of per-sonality related anxiety among physically active obese adults. However, larger samples are required for firmer conclusions.